2017
DOI: 10.1016/j.cct.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Using social media to deliver weight loss programming to young adults: Design and rationale for the Healthy Body Healthy U (HBHU) trial

Abstract: Background The transitional period from late adolescence to early adulthood is a vulnerable period for weight gain, with a twofold increase in overweight/obesity during this life transition. In the United States, approximately one-third of young adults have obesity and are at a high risk for weight gain. Purpose To describe the design and rationale of a National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) sponsored randomized, controlled clinical trial, the Healthy Body Healthy U (HBHU) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 69 publications
(72 reference statements)
1
33
0
Order By: Relevance
“…Searches were re-run in March 2018, which led to an additional three articles suitable for full text review. 2729 Articles were excluded due to relating to wrong outcomes (e.g. cardiovascular risk, BMI), wrong study design (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Searches were re-run in March 2018, which led to an additional three articles suitable for full text review. 2729 Articles were excluded due to relating to wrong outcomes (e.g. cardiovascular risk, BMI), wrong study design (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Tailoring input, which provided the basis for the process of tailoring was gathered using online questionnaires at baseline, 31,32 web-based diaries, 33 via purpose-built tailored website, 33 study-designed mobile applications, 30 SMS messaging, 29 Facebook, and emails from a remote health coach. 30…”
Section: Resultsmentioning
confidence: 99%
“…Content and delivery (e.g., social networking, text messaging) was also modeled after the digital weight loss intervention developed by Napolitano et al [40,55]. This included tailoring each lesson topic to the environmental context of having a new baby, as well as the social, cultural and environmental context and needs identified in our Phase 1 formative work.…”
Section: Methodsmentioning
confidence: 99%
“…For example, one study using social media to connect with 13 participants found a positive correlation between interaction on social media, comments/likes, and weight changes. (Prout Parks E, 2018) Other studies are currently underway to determine if social media and online use can be used to assist young adults with reaching a wider audience to assist with weight management (Napolitano MA, 2017).…”
Section: Discussionmentioning
confidence: 99%